ANALISIS PERBEDAAN KEPATUHAN WAJIB PAJAK DAN PENERIMAAN PAJAK RESTORAN KOTA BEKASI SEBELUM DAN SESUDAH PEMERIKSAAN PAJAK - Fajarwati, Diana; Tusilandari, Evi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2012)
The purpose of research to determine: (1) Restaurant taxpayer compliance, (2) Restaurant Tax receipts, (3) whether there are significant differences in taxpayer compliance before and after the inspection taxes, and (4) whether there are significant differences Restaurant Tax receipts before and after tax audit. The research uses descriptive quantitative method with a comparative approach. Samples were DPPKAD tax inspectors and taxpayers Bekasi Restaurants that use self-assessment system and have been checked by the year 2008 DPPKAD Bekasi taxpayers as much as 8 Restaurant. Purposive sampling technique using the method of sample. Data collection using questionnaires and documentation. The results obtained: (1) of the tax by DPPKAD Bekasi consists of two stages, namely: (a) phase checker, which went to the restaurant, do analysis, and send mail tax bills, and (b) phase of the audit, namely: inspect and examine documents, submit a letter of reprimand, conduct field checks, and (4) complete the examination, (2) compliance with the taxpayer before the close to both Restaurants (score 3.73) and after close examination of both (score 3.98), (3) Average Restaurant Tax receipts prior to the examination = Rp 31,568,883, - (2006) and in 2007 increased 6.32%, 8.36% rise time of examination, following a 7.54% increase (in 2009) and 3, 48% (in 2010), (4) there are differences in taxpayer compliance before and after the examination (t-hit = - 2.671, sig. 0.011), and (5) there are differences in the average tax receipts Restaurant two years before and after the examination (t-hit = - 15.097, sig. 0.000), one year before and during the examination (t-hit = - 2.674, sig. 0.032), and the time of examination and inspection after one year (t-hit = - 3.673, sig. 0.008). Suggestions submitted to DPPKAD Bekasi are: (1) objectivity and professionalism of the tax to be further enhanced through the establishment of a clear standard of examination and improvement of technical education and skills of tax inspectors, (2) the effectiveness of monitoring the performance of tax inspectors to be more enhanced, and (3) compliance with the taxpayer to be further enhanced through intensive counseling taxes.